2015
DOI: 10.1097/mco.0000000000000192
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon – the new ‘insulin’ in the pathophysiology of diabetes

Abstract: Purpose of review Autoimmune destruction of the b cells is considered the key abnormality in type 1 diabetes mellitus and insulin replacement the primary therapeutic strategy. However, a lack of insulin is accompanied by disturbances in glucagon release, which is excessive postprandially, but insufficient during hypoglycaemia. In addition, replacing insulin alone appears insufficient for adequate glucose control. This review focuses on the growing body of evidence that glucagon abnormalities contribute signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 121 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…Subsequent studies showed that somatostatin-induced inhibition of postprandial glucagon secretion ameliorates hyperglycemia in patients with T2D (Gerich et al, 1974;Dinneen et al, 1995;Shah et al, 2000), and more recently that blocking glucagon action decreases hyperglycemia in a variety of species, including rodents (Mu et al, 2011;Kim et al, 2012b;Okamoto et al, 2017), rabbits (Brand et al, 1996), dogs (Rivera et al, 2007), nonhuman primates (Xiong et al, 2012;Okamoto et al, 2015), and humans (Petersen and Sullivan, 2001;Kelly et al, 2015;van Dongen et al, 2015;Kazda et al, 2016;Kostic et al, 2018). The virtues and limitations of antagonizing glucagon signaling for the treatment of diabetes have recently been highlighted in several review articles (Unger and Cherrington, 2012;Farhy and McCall, 2015;Lee et al, 2016b;Müller et al, 2017), with the implication that excess glucagon action can serve a greater role in the pathology of T2D than impaired insulin action (Unger and Cherrington, 2012). In summary, there is substantial evidence directing inhibition of glucagon action as opposed to enhancing it for the treatment of T2D.…”
Section: A Glucagon-like Peptide 1/glucagon Coagonismmentioning
confidence: 99%
“…Subsequent studies showed that somatostatin-induced inhibition of postprandial glucagon secretion ameliorates hyperglycemia in patients with T2D (Gerich et al, 1974;Dinneen et al, 1995;Shah et al, 2000), and more recently that blocking glucagon action decreases hyperglycemia in a variety of species, including rodents (Mu et al, 2011;Kim et al, 2012b;Okamoto et al, 2017), rabbits (Brand et al, 1996), dogs (Rivera et al, 2007), nonhuman primates (Xiong et al, 2012;Okamoto et al, 2015), and humans (Petersen and Sullivan, 2001;Kelly et al, 2015;van Dongen et al, 2015;Kazda et al, 2016;Kostic et al, 2018). The virtues and limitations of antagonizing glucagon signaling for the treatment of diabetes have recently been highlighted in several review articles (Unger and Cherrington, 2012;Farhy and McCall, 2015;Lee et al, 2016b;Müller et al, 2017), with the implication that excess glucagon action can serve a greater role in the pathology of T2D than impaired insulin action (Unger and Cherrington, 2012). In summary, there is substantial evidence directing inhibition of glucagon action as opposed to enhancing it for the treatment of T2D.…”
Section: A Glucagon-like Peptide 1/glucagon Coagonismmentioning
confidence: 99%
“…Glucagon contributes to hyperglycemia in diabetes by increasing hepatic glucose output, and antagonizing glucagon's actions has been an appealing strategy to reduce glycemia [7,8]. Indeed, glucagon receptor antagonists lower blood glucose in clinical and experimental diabetes [9,10], and deletion of the gene for glucagon or the glucagon receptor, globally or liver-specific, results in slightly lower blood glucose levels in mice [11][12][13].…”
Section: Disruption Of Glucagon Receptor Signaling Improves Glycemia ...mentioning
confidence: 99%
“…Furthermore, some diabetic patients show abnormally high concentrations of insulin in the blood, insulinaemia, since more insulin is required to stimulate desensitized insulin receptors undergoing insulin resistance. In addition, a paradoxically high concentration of glucagon in the blood, glucagonaemia, is also observed in hyperglycaemia under diabetes [167][168][169]. However, beyond the absolute levels of physiological quantities, rhythmic processes and their synchronization must have additional information in physiology [170].…”
Section: Rhythm and Phasementioning
confidence: 99%
“…However, later research became insulin-centric with an emphasis on β cells. Nevertheless, the importance of the balance between insulin and glucagon or a glucagonocentric view has been continuously mentioned with the abnormal functions of α cells in diabetes [167][168][169][184][185][186]. Recently, islet biologists have resumed emphasizing the role of δ cells in glucose control [187][188][189], which was reported 40 years ago [190,191].…”
Section: Complex Systemsmentioning
confidence: 99%